PEMBELAJARAN JARAK JAUH KEGIATAN AMALIYAH BULAN RAMADHAN MASA PANDEMI COVID-19 - Mujahidatul Haibah; Rochman, Chaerul; Farida, Ida (UIR Press, 2021)
This research reveals the problems that occur during distance learning in the amaliyah activities in the month of Ramadan during the Covid-19 pandemic at 16 Bandung Public High Schools. At the same time, the purpose of this study is to find distance-learning about the activities of the Islamic month of Ramadan during the Covid-19 pandemic at 16 Bandung Public High Schools. This research is a qualitative descriptive study based on a sample consisting of 22 men and 13 women, using the instruments, namely a checklist and a matrix, in triangulation questions. Data analysis techniques include providing value, calculating the average number of scores, calculating the average according to gender, calculating the relationship of 3 variables; graphs, triangulation illustrate the results. Based on the data analysis conducted, the results of this study are strong in the ability of the character components of students or students who, on average, get the highest score or value. And also that the distance learning process about the amaliyah activities of the month of Ramadan during the Covid-19 pandemic at SMAN 16 Bandung school can better shape the character of students or students. This research concludes that learning during this pandemic period; students have more expertise in competency components. And with this character and product relationship can make good results.